Convalescence: rehabilitation needs more attention. Issue 11 (25th May 1973) - Unknown
Abstract : Rehabilitation is an active process used to help regain particular functions and is the most specific component of convalescence. It is a part of medicine in general and touches all aspects of patient care. For example chronic chest infection requires postural drainage, breathing exercises and cough training; cardiac infarction, a programme of graded activity to increase exercise tolerance; injury to bones and joints may require physiotherapy, hydrotherapy and occupational therapy.